Intervensi PELINDUNG: Pencegahan ISPA Bagi Anak dan Remaja di LKSA Panti Asuhan Berkah Kota Palangka Raya, Kalimantan Tengah - Aloysia Ispriantari; Musthika Wida Mashitah (Jurnal Informasi Pengabdian Masyarakat, 2026)
The high number of Acute Respiratory Infections (ARI) in Indonesia, driven by environmental factors and the vulnerability of the child population, is a serious concern. Children and adolescents in Child Welfare Institutions (LKSA) are at high risk due to crowded conditions and limited facilities. This community service activity aims to increase awareness and practice of ARI prevention among children at the LKSA Panti Asuhan Berkah Palangka Raya. The "PELINDUNG" intervention adopted a comprehensive approach, including the distribution of masks and handwashing soap, as well as interactive health education. Educational materials covered ARI, 6-step Handwashing with Soap (CTPS), and demonstrations of correct mask use, delivered through posters and hands-on practice. Data on participation and initial responses were collected during the activity. The program successfully reached approximately 70 children and adolescents at the LKSA Panti Asuhan Berkah, who demonstrated active participation and positive responses. The provision of essential health facilities was also well received. Results indicated increased awareness and understanding of ARI prevention among participants. This community-based intervention was effective in improving preventive behaviors in vulnerable communities. It is hoped that more structured health support and regular evaluation of educational sustainability can continue to be implemented to improve the health of children and adolescents in LKSA.